2016
DOI: 10.1111/jwas.12283
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture Techniques for Crappie, Pomoxis spp., Culture

Abstract: Extensive crappie, Pomoxis spp., culture has been practiced for decades, however, knowledge of crappie aquaculture methods is limited. The following review synthesizes existing research on crappie aquaculture and identifies knowledge gaps where further research is needed. Topics such as life history, tank culture, feeding, reproduction and spawning, larval rearing, transport and harvest, triploidy, hybridization, and out-of-season spawning were reviewed. The outcome is a better understanding of hindrances prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Farmers and state/federal hatcheries have been producing crappies for recreational markets and for stocking public or state‐managed lakes and reservoirs for decades, but overall knowledge of pond production techniques for crappies remains fairly limited (Culpepper and Allen ). Hybrid crappies have demonstrated superior growth (Smith et al.…”
mentioning
confidence: 99%
“…Farmers and state/federal hatcheries have been producing crappies for recreational markets and for stocking public or state‐managed lakes and reservoirs for decades, but overall knowledge of pond production techniques for crappies remains fairly limited (Culpepper and Allen ). Hybrid crappies have demonstrated superior growth (Smith et al.…”
mentioning
confidence: 99%
“…While already a diverse food production sector, the ongoing research on aquaculture of many new species will likely result in even greater numbers of aquatic species in commercial production by 2050. Recent examples in the Journal of the World Aquaculture Society ( JWAS ) on culture techniques for species that are newer candidates for commercial production include: seahorses (Martínez‐Cardenas and Purser ; Qin et al ; Wang et al ), knifejaw (Biswas and Takii ), Chu's croaker (Huang et al ), crappie (Culpepper and Allen ), peppermint shrimp (Calvo et al ), spotted ivory shell (Lü et al ), painted river prawn (Gomes et al ), rabbitfish (Pham and Le ), and starry and southern flounder (Hu et al ; Song et al ).…”
mentioning
confidence: 99%
“…Studies using adult crappie in tank culture systems have been hindered by disease-related mortality. Disease outbreaks have been attributed to bacterial infections, notably Flavobacterium columnare and Aeromonas spp., which commonly affect adult crappies collected from natural systems in the first 2 weeks after their transfer to tanks (Smeltzer and Flickinger 1991;Culpepper and Allen 2016). Recent advances indicate that acclimation conditions can minimize disease by using cool temperatures (~15°C) and low salinity (3-5 ppt; Culpepper and Allen 2016).…”
mentioning
confidence: 99%
“…However, these studies did not conduct comparative experiments to determine the culture conditions and most effective hormone for inducing spawning in adult crappies. A recent spawning experiment on White Crappies (Culpepper and Allen 2016) found that ovulation can be induced in tanks by using salmonid gonadotropin-releasing hormone analog (GnRHa; 0.5 mL/kg) or LHRHa (100 μg/kg). Collectively, these studies facilitate the investigation of spawning crappies out of season.…”
mentioning
confidence: 99%
See 1 more Smart Citation